Surgical treatment of mucocele in an 11 month-old baby: a case report. - Cunha, Robson Frederico [UNESP]; De, MelloVieiraAnaElisa; Carvalho, PugliesiDanielaMaria; Guimaraes, Correia Monique; Macedo, Crivelini Marcelo (My University, 2002)
The present report describes the occurrence of mucocele in the lower lip of an 11 month-old baby. The treatment instituted was the excision of the lesion. Microscopic examination confirmed the diagnosis of mucocele. Three months after surgery, no sign of recurrence was observed.
Keywords: case report; human; infant; lip disease; male; mucocele; Humans; Infant; Lip Diseases; Male; Mucocele